Interventions that facilitate sustainable development by preventing toxic exposure to chemicals: an overview of systematic reviews - Michelle M. Haby; Agnes Soares; Evelina Chapman; Rachel Clark; Marcelo Korc; Luiz A. C. Galvão
ABSTRACT Objective To identify interventions that 1) facilitate sustainable development by preventing toxic exposure to chemicals, including pesticides, and 2) have a positive impact on health. Methods This overview utilized systematic review methods to synthesize evidence from multiple systematic reviews and economic evaluations. A comprehensive search was conducted based on a predefined protocol, including clear inclusion criteria. To be classified as "sustainable" interventions needed to aim (explicitly or implicitly) to 1) have a positive impact on at least two key dimensions of the United Nations integrated framework for sustainable development and 2) include measures of health impact. Results Thirteen systematic reviews and two economic evaluations met the inclusion criteria. The interventions that were most likely to have a positive impact on health included 1) legislation to ban Endosulfan pesticide to prevent fatal poisonings; 2) testing of drinking water for contamination with arsenic, and dissemination of the results to households; and 3) implementation of organic farming / diet to reduce exposure to pesticides. However, the cost-effectiveness of these three interventions and their impact(s) on health inequalities is not known. Strict enforcement of interventions to reduce lead in houses with children was cost-beneficial. Education and dust control interventions performed by cleaning professionals to reduce blood lead levels in children were ineffective. Conclusions What is needed now is careful implementation of the interventions whose impacts are likely to be positive. Ineffective interventions need to be replaced with more effective and cost-effective interventions. Finally, more and better-quality research on the prevention of toxic exposure to chemicals is needed to better support policy development.